Pengaruh Citra Merek dan Akses Lokasi terhadap Minat Berkunjung Tamu pada Hotel Santika Sukabumi - Dendi Zainuddin Hamidi; Noornissa Sarah Ginanjar; Galih Hidayat; Susanto Susanto; Besar Agung Martono (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of brand image and location access on the guest visiting intention at Hotel Santika Sukabumi, either partially or simultaneously. The population is all potential tourists in the city of Sukabumi whose number cannot be known with certainty. A sample of 99 people was taken. Determination of the sample size using the Cochran formula. The sampling technique chosen is incidental sampling. Primary data collection was carried out by distributing electronic questionnaires within one month (cross section). The collected primary data was processed by multiple linear regression analysis. It was found that brand image partially has a significant effect on guest visiting intention at Hotel Santika Sukabumi, location access partially does not have a significant effect on guest visiting intention at Hotel Santika Sukabumi, brand image and location access simultaneously have a significant influence on the guest visiting intention at Hotel Santika Sukabumi where 52.5% of variations in guest visiting interest at Hotel Santika Sukabumi can be explained by variations in brand image and location access.